Continuous 3D Titanium Nitride Nanoshell Structure for Solar‐Driven Unbiased Biocatalytic CO2 Reduction. Issue 25 (17th May 2019) - Kuk, Su Keun; Ham, Youngjin; Gopinath, Krishnasamy; Boonmongkolras, Passarut; Lee, Youngjun; Lee, Yang Woo; Kondaveeti, Sanath; Ahn, Changui; Shin, Byungha; Lee, Jung‐Kul; Jeon, Seokwoo; Park, Chan Beum
Abstract: Z‐scheme‐inspired tandem photoelectrochemical (PEC) cells have received attention as a sustainable platform for solar‐driven CO2 reduction. Here, continuously 3D‐structured, electrically conductive titanium nitride nanoshells (3D TiN) for biocatalytic CO2 ‐to‐formate conversion in a bias‐free tandem PEC system are reported. The 3D TiN exhibits a periodically porous network with high porosity (92.1%) and conductivity (6.72 × 10 4 S m −1 ), which allows for high enzyme loading and direct electron transfer (DET) to the immobilized enzyme. It is found that the W‐containing formate dehydrogenase from Clostridium ljungdahlii (ClFDH) on the 3D TiN nanoshell is electrically activated through DET for CO2 reduction. At a low overpotential of 40 mV, the 3D TiN‐ClFDH stably converts CO2 to formate at a rate of 0.34 µmol h −1 cm −2 and a faradaic efficiency (FE) of 93.5%. Compared to a flat TiN‐ClFDH, the 3D TiN‐ClFDH shows a 58 times higher formate production rate (1.74 µmol h −1 cm −2 ) at 240 mV of overpotential. Lastly, a bias‐free biocatalytic tandem PEC cell that converted CO2 to formate at an average rate of 0.78 µmol h −1 and an FE of 77.3% only using solar energy and water is successfully assembled. Abstract : A conductive 3D TiN nanoshell electrode is developed for biocatalysis‐coupled photoelectrochemical cells that reduce CO2 through direct electron transfer driven by solar energy without any external bias. The tandem cell structure provides sufficient photovoltage to gain electrons from solar water oxidation, to transport electrons to the 3D biocathode, and to inject electrons into formate dehydrogenase.